Magnetic Ferrites Synthesized from Leclanché Exhausted Batteries for Heavy Metal Detection - Santiago Kosloski; Jarem Raul Garcia; Alan Fernando Yoshiaki Matsushita (Orbital: The Electronic Journal of Chemistry)
The pervasive presence of heavy metals in the environment poses significant health risks, necessitating the development of efficient and cost-effective detection methods. This study explores the use of MFe2O4-based nanocomposites, synthesized from exhausted Leclanché cell residues, for the electrochemical detection of heavy metals such as Cu2+, Hg2+, Pb2+, and Sn2+. The nanocomposites were modified with silica (SiO2) using tetraethyl orthosilicate (TEOS) to enhance their functional properties, particularly for improved stability and surface functionality crucial for environmental applications. Comprehensive characterization techniques including XRD, FTIR, SEM, TEM, and DLS confirmed the successful synthesis and modification of the nanoparticles. Electrochemical assessments demonstrated the nanocomposites capability to detect heavy metals with good sensitivity, validated through Differential Pulse Stripping Voltammetry (DPSV). This preliminary study not only proves the efficacy of MFe2O4@SiO2 in detecting individual heavy metals but also sets the groundwork for future research on their application in real-world environmental samples and mixed-metal scenarios. The advancement of such nanotechnology-based sensors represents a promising approach to enhancing public health and environmental safety protocols.